RESISTIRE D4.4: Summary report on qualitative indicators - Kent, Alexandra; Strid, Sofia; Sandström, Lina; Callerstig, Anne-Charlotte (Zenodo, 2023)
The aim of RESISTIRÉ is to understand the unequal impacts of the COVID-19 outbreak and its policy and societal responses on behavioural, social and economic inequalities and to work towards individual and societal resilience. RESISTIRÉ does so by collecting and analysing policy data, quantitative data and qualitative data in the EU27 (except Malta), Iceland, Serbia, Turkey and the UK, and translating these into insights to be used for designing, devising and piloting solutions for improved policies and social innovations, which in turn can be deployed by policymakers, stakeholders and actors in the field across different policy domains. This project process is repeated in three cycles, each step and cycle feeding the next one. Throughout the course of the three project cycles, research has consistently shown that already vulnerable and marginalised groups have become even more vulnerable and marginalised; existing inequalities have increased, and new ones have emerged (Axelsson et al. 2021; Cibin et al. 2021, 2022; 2023; Harroche et al. 2023; Sandström et al. 2022, 2023; Stovell et al. 2021, 2022). This report summarises the main findings from each of the three research cycles of qualitative indications of inequalities (previously published in Axelsson et al., 2021, Sandström et al. 2022, and Sandström et al. 2023). In total, it builds on 793 narratives from interviews with 741 individuals about their personal experiences during COVID-19, 14 pan-European workshops with 209 inequality experts and representatives from civil society, public authorities, and academia, and 71 semi-structured interviews with experts in public authorities. The areas where the impact of the pandemic outbreak on inequalities were explored are drawn from the policy domains in the EU Gender Equality Strategy (EC, 2020), and the fundamental human rights and environmental justice domains (the latter from the Beijing Platform for Action, 1995) including: gender-based violence; work and labour market; economy, gender pay and pension gap; ...